MIGRATION PROCESSES IN MODERN DAGESTAN: PERIODIZATION AND ETHNOSOCIAL CONTEXT - Kurbanov, Magomedzagir Usupovic; Gimbatov, Samil' Magomedovic (History, Archeology and Ethnography of the Caucasus, 2023)
The paper explores the history of migration processes in the Republic of Dagestan and their impact on the formation of the ethnic structure and socio-economic development of the region. The work provides an overview of different periods of migration and population relocation within the context of political, economic, and social processes. Various research methods, including the analysis of historical sources, statistical data, and expert assessments, are employed. The paper highlights the close connection between migration processes and socio-economic and ethnopolitical changes in the region from the 20th to the early 21st centuries. It particularly emphasizes the large-scale wave of resettlement of the mountain population to the lowlands in the initial years of Soviet power, the periods of Chechen and Ingush deportation in 1944, mass internal migration from villages to cities and other regions of Russia in the late 1980s to early 1990s, and the strengthening of labor migration due to deindustrialization and rising unemployment in various sectors of the economy since the 2000s. The paper also examines different aspects of migration processes in Dagestan during the 20th century. It delves into socio-economic changes in the region, focusing on the resettlement of mountaineers to lowland areas in the first half of the 20th century. Special attention is given to the settlement of Dagestanis on the lands of deported peoples, migration of livestock farmers in neighboring regions, movement of the population affected by the earthquakes, and the intensification of seasonal migration processes. The paper also addresses the emergence of ethnosocial tension and forced migration processes in the region during the 1990s. It analyzes the influence of migration on the dynamics and structure of the settlement of peoples and the ethnic composition of the population. The paper uncovers a close relationship between migration processes and socio-economic changes in Dagestan from the 20th to the early 21st centuries. The conclusion drawn highlights the multifaceted and intricate nature of migration processes in Dagestan. The conducted analysis enables an assessment of the scale and dynamics of socio-economic and ethnopolitical changes in the region.